Listen, the Landscape: The Nature Narratives in Jacob Ross’ Short Story Collection Tell No-One About This - Ramos-Rodriguez, Michelle (Il Tolomeo, 2020)
Ross, J. (2017). Tell No-One About This. England: Peepal Tree.